Internal Audit of Food and Beverage Inventory at Astagina Resort Villa and Spa Legian (Case Study of January and March 2018) - M M Purwaniwati; D P Suciwati; C Ardina (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
This study aims to test the internal audit which is divided into operational audit and financial audit of food and beverage inventory at Astagina Resort Villa & Spa Legian. During this time, there is always variance in the inventory of food and beverage between the amount of the system and the physical amount The primary data are accounting system of purchase and sale of food and beverage inventory and how to calculate the ending balance of food and beverage inventory. The secondary data are standard operational procedure, organizational structure, result of physical calculation and record of physical quantity of supply of food and beverages in January and March 2018. Descriptive qualitative and quantitative is as a analytical technique. The results of the operational audit show weaknesses in the Company's Internal Control System such as do not use copy of the form, the absence of a surprise audit, the absence of job rotation, and the company does not entablishment of an internal supervisory unit. While the results of financial audits indicate the difference of more and less on the physical calculation of inventory with the record.